Self-organizing spectrum allocation (SON-SA) scheme for heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Hashim, Wahidah; Khan, Sheroz (Science and Knowledge Research Society, 2014)
In Heterogeneous Network (HetNet), Femtocells (HeNodeBs) are deployed due to extension of coverage and sophisticated spectrum effectiveness in indoor environment. However, the random deployment of HeNodeBs may create the co-channel interference (CCI) with macrocell (meNB) users, thereby a service disruption occurred. To mitigate CCI a SON-SA is proposed in this paper. In order to maximize the downlink throughput the proposed scheme will regulate the subcarrier power in OFDM to diminish CCI. To manage the CCI, the proposed scheme is applied the energy detection (ED) for sub-carrier bands detection, and sub-channel as well as power allocation scheme is adopted Karush-Kuhn-Tucker (KKT) condition in the sub-carrier level to allocate power. The simulation results represents that SON-SA is able to maximize the downlink throughput through alleviating the CCI from underlay HetNet.